MicroRNA‐200b is a potential biomarker of the expression of PD‐L1 in patients with lung cancer. Issue 10 (7th September 2020) - Katakura, Seigo; Kobayashi, Nobuaki; Hashimoto, Hisashi; Kamimaki, Chisato; Tanaka, Katsushi; Kubo, Sousuke; Nakashima, Kentaro; Teranishi, Shuhei; Manabe, Saki; Watanabe, Keisuke; Horita, Nobuyuki; Hara, Yu; et al.
Abstract : Background: Advanced non‐small cell lung cancer (NSCLC) has a high mortality rate and poor prognosis. However, outcomes have gradually improved after the introduction of novel immunotherapies, including immune checkpoint inhibitors (ICIs). Although programmed death‐ligand 1 (PD‐L1) expression in tumor tissues is a known biomarker for guiding ICI treatment of NSCLC, challenges such as difficulty of liquid biopsy and heterogeneous results during treatment persist. This study evaluated the potential of miR200b as a surrogate biomarker for PD‐L1 expression. Methods: We used the human lung cancer cell lines H226, H460, H520, A549, and H1975. miR200b expression in blood and bronchoscopy specimens of NSCLC patients was evaluated using reverse‐transcription‐quantitative PCR. Using flow cytometry, PD‐L1 expression in vitro, as well as in tumor tissues, was evaluated after transfection with a mimic miR200b or siRNA. Results: miR200b expression negatively correlated with PD‐L1 expression in all cell lines. The induction or knockdown of miR200b also altered PD‐L1 expression in vitro. The patient group with a PD‐L1 tumor proportion score ≥ 50% had significantly lower miR200b expression in the bronchoscopy specimens ( P = 0.025) and serum‐derived exosomes ( P = 0.022) than that with PD‐L1 tumor proportion score < 50%. Conclusions: miR200b can regulate PD‐L1 expression in lung cancer cells, and miR200b expression in clinical specimens negatively correlated with PD‐L1 expression. Thus, miR200b may be a useful surrogate biomarker for PD‐L1 expression in lung cancer patients. Key points: Significant findings of the study: High PD‐L1 expression was linked to low miR200b expression, whereas low PD‐L1 expression was linked to high miR200b expression in human lung cancer patients. Thus, miR200b overexpression or silencing can control PD‐L1 expression in cancer cells. What this study adds We demonstrated the potential of miR200b as a surrogate biomarker for PD‐L1 expression in lung cancer patients. Abstract : Relative to patients with a PD‐L1 tumor proportion score of <50%, patients with a PD‐L1 tumor proportion score of =50% had significantly lower miR200b expression in the bronchoscopy specimens and serum‐derived exosomes.